Efeito de dentifrícios com sílica bioativa no esmalte bovino erodido : estudo in vitro - Sousa, Elizabeth Barreto Galvao de (2024)
Introduction: Dental erosion is a chronic non-bacterial disease caused by continuous contact with acidic substances, leading to the progressive loss of dental structure. With increasing prevalence and a negative impact on aesthetics and function, its worsening can occur with abrasion and attrition. The REFIX® technology, containing tetrasodium pyrophosphate and silica, emerges as a promising therapeutic alternative, promoting remineralization and reducing dental solubility. Thus, the addition of compounds to fluoride or its replacement with alternatives in dentifrices shows potential for the remineralization of dental erosion lesions. Objectives: To evaluate the impact of REFIX® technology toothpastes with or without different concentrations of fluoride on the surface hardness and mineral gain of eroded enamel surfaces. Materials and methods: Sixty Enamel blocks were randomly distributed into five groups (n=12/group): RGS1 (REFIX®-toothpaste with 1450 ppm F), RGS2 (REFIX® -toothpaste with 1100 ppm F), RGS3 (fluoride-free REFIX®-toothpaste), negative control-NC (fluoride-free toothpaste), and positive control-PC (1100 ppm F toothpaste). The enamel blocks were divided into three thirds: intact (untreated), eroded (demineralized lesion), and treated (erosion lesion, pH cycling with dentifrices). The specimens were submitted to an erosive pH cycling model for 5 days. The erosive challenge was performed 4 times/day (90s), and after the first and last cycles, the specimens were treated with toothpaste slurries (1:3) for 2 minutes. Surface microhardness was measured in sound (SH0), eroded (SH1), and treated (SH2) areas, and the percentage of surface microhardness change (%SMHC) was calculated. Following treatment, fluorescence loss was measured by Quantitative Light-Induced Fluorescence (QLF) between ΔF1 (sound-eroded area) and ΔF2 (sound-treated area). The mineral fluorescence gain (ΔFg) was calculated using the difference between ΔF2 and ΔF1. Data were statistically analyzed by ANOVA followed by Tukey’s test (p<0.05). Results: All dentifrices had a significant impact on enamel surfaces. REFIX® technology toothpastes were more effective in enamel rehardening and mineral gain after treatment (p<0.05). The %SMHC ranking was as follows: RGS2 > RGS1> RGS3 = PC > NC. The fluorescence gain (ΔFdif) ranking was: RGS2 = RGS1 =RGS3 > PC > NC. The NC group showed a loss of surface hardness and mineral fluorescence after treatment, demonstrating no efficacy in mineral gain or surface rehardening.The CN group had the highest surface roughness after treatment. The other groups (RGS and CP) had the highest surface smoothness after use (p<0.05). The CN group also had the highest tooth surface loss compared to the others (p<0.05). The RGS1, RGS2, RGS3 and CP toothpastes had similar values (p<0.05). Conclusions: REFIX® technology toothpastes showed greater efficacy in improving surface hardness and mineral gain in the treatment of eroded enamel.